Rast podjetniške aktivnosti v Sloveniji: GEM Slovenija 2008 - Rebernik, Miroslav; Tominc, Polona; Pušnik, Ksenja (University of Maribor Press, 2009)
Growth of Entrepreneurial Activity in Slovenia : GEM Slovenia 2008. In this publication we differentiate between the factor-driven economies, where the development is based on exploiting basic natural resources, the efficiency-driven economies, where the development is based on an efficient exploitation of these resources, and the innovation-driven economies, whose development is based on innovations. In all three types of economies – factor-driven, efficiency-driven and innovation-driven – we deal with three fundamental elements of entrepreneurship, i.e. the attitude towards entrepreneurship, the entrepreneurial activity and growth aspirations. In the next year, Slovenia may expect a decrease in early-stage entrepreneurial activity. That is, it is unlikely to expect that a large number of newly unemployed individuals could set up a business because of the decrease of business opportunities and the fact that the rate of necessity driven entrepreneurship in Slovenia is very low. We can also expect a decrease in entrepreneurial aspirations as the economic crisis will lessen the optimistic expectations of entrepreneurs. Regardless of the crisis and economic policy instruments that have to be adapted to it, more emphasis should be devoted to stimulate a dynamic, growth-oriented entrepreneurship, which is more than necessary for Slovenia to make further development steps.